2021
DOI: 10.1192/bjo.2021.64
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal contraceptive use and depressive symptoms: systematic review and network meta-analysis of randomised trials

Abstract: Background Observational studies suggest that hormonal contraceptive use may increase depressive symptoms in women, but it is unclear whether the effect is causal. Aims To quantitatively examine the evidence from randomised clinical trials for the link between hormonal contraceptive use and depressive symptoms. Method We performed a systematic review and network meta-analysis of randomised clinical trials comparing women randomised to any form of a hormonal contraceptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…While depressive symptoms as an outcome was beyond the scope of the current study, it is important to note that the association between hormonal contraception use and the subsequent development of depressive symptoms has been mixed (de Wit et al, 2021; Zettermark et al, 2018). In understanding this relationship, it may be important to consider the role of baseline depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While depressive symptoms as an outcome was beyond the scope of the current study, it is important to note that the association between hormonal contraception use and the subsequent development of depressive symptoms has been mixed (de Wit et al, 2021; Zettermark et al, 2018). In understanding this relationship, it may be important to consider the role of baseline depression.…”
Section: Discussionmentioning
confidence: 99%
“…Articles were excluded if they did not meet the above criteria. In addition, because research has found associations between the use of hormonal contraception and subsequent depression to be mixed (de Wit et al, 2021; Zettermark et al, 2018) and unrelated to the scope of the current review, we excluded articles that analyzed data with depression or anxiety as an outcome variable. We also excluded articles in which the outcome only assessed the consistency of condom use as there have been many studies looking at this outcome variable, and this review was focused on females’ use of nonbarrier contraception.…”
Section: Methodsmentioning
confidence: 99%
“…This study was unable to comment on why women on mood stabilisers preferentially used non-hormonal contraception; however, a possible explanation may have concerns regarding potential effects on mood as previously discussed. 24 , 25 Teratogen use was common, with 41.8% ( n = 79) of women prescribed a teratogen; however, teratogen prescription did not influence contraception usage (Fisher’s exact test, p = 0.531) ( Table 2 ). International guidelines recommend that women using teratogenic medication receive FPE and some teratogenic medication, such as valproate, is contraindicated unless women have had FPE as part of the valproate pregnancy prevention plan.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of consensus in previous studies as to the effect of HC on psychological well-being, with evidence existing for both adverse and favorable mental health outcomes after HC use (34,35). Recent reviews have reported a general lack of association between HC use and depression symptoms (36,37). Our findings agree with this position as we did not observe differences in depression or anxiety symptoms between HC+ and HC− groups at any time point.…”
Section: Discussionmentioning
confidence: 99%